2013
DOI: 10.5539/apr.v5n1p7
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Analysis of the Quantum Relativistic Motion of an Electron

Abstract: Based on Pauli spin matrices, this paper settles the geometry of our previously constructed combined spacetime 4-manifold to be {(t+ti, x+yi, y+zi, z+xi): (t,x,y,z) of Minkowski space} locally. Thereby we specify the motions of the two eigenvectors of the spin operator and show that they satisfy Dirac equation of a free electron; accordingly, an electron is a point particle born out of a spinning classic electric field with each of its energy density points rotating along two perpendicularly connected semi-cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This paper extends our previous analysis of a free electron-wave (Light, 2013), where we showed its motion being that around two perpendicularly connected semi-circles by casting Pauli matrices in the Dirac equation in our proposed combined spacetime 4-manifold as …”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…This paper extends our previous analysis of a free electron-wave (Light, 2013), where we showed its motion being that around two perpendicularly connected semi-circles by casting Pauli matrices in the Dirac equation in our proposed combined spacetime 4-manifold as …”
Section: Introductionsupporting
confidence: 63%
“…By providing all fermions and bosons with the geometrices of their wave motions, we have amplified the quark model for an explanation of the hundreds' varieties of nuclear particles, all via different superpositions of the electromagnetic fields in the cosmic black hole B contained in the wave universe M [2] (see Light, 2013, Equation (1.1)). To be sure, our mathematical framework permits non-quark particles by admitting additional angles between the two semi-circles mentioned above, such as 45 degrees, in which case, the electric charge 1 / 2   (cf.…”
Section: Summary Remarkmentioning
confidence: 99%
“…Since we have established the unique electromagnetic wave length λ * = 2.56 × 10 −35 meter at t [1] 0 = 0, we now proceed to show how photon-waves could create electron-waves. As this section depends greatly on our forthcoming paper [11], we will present our arguments in a series of remarks more verbally. [10], we showed that the motion of an electromagnetic wave A with energy E [3] (before Big Bang) had the following equation:…”
Section: Pair-creation Of Electron and Positronmentioning
confidence: 99%
“…In our forthcoming paper [11] we have shown that the electromagnetic wave associated with an electron spins along two semi-circles that are perpendicularly connected to each other by solving the Dirac equation for the two eigenvectors of the spin operator for a free electron. We found that Pauli matrices…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation